Disorder-specific effects of polymorphisms at opposing ends of the Insulin Degrading Enzyme gene - Bartl Jasmin; Scholz Claus-Jürgen; Hinterberger Margareta; Jungwirth Susanne; Wichart Ildiko; Rainer Michael K; Kneitz Susanne; Danielczyk Walter; Tragl Karl H; Fischer Peter; Riederer Peter; Grünblatt Edna (BMC, 2011)
Abstract Background Insulin-degrading enzyme (IDE) is the ubiquitously expressed enzyme responsible for insulin and amyloid beta (Aβ) degradation. IDE gene is located on chromosome region 10q23-q25 and exhibits a well-replicated peak of linkage with Type 2 diabetes mellitus (T2DM). Several genetic association studies examined IDE gene as a susceptibility gene for Alzheimer's disease (AD), however with controversial results. Methods We examined associations of three IDE polymorphisms (IDE2, rs4646953; IDE7, rs2251101 and IDE9, rs1887922) with AD, Aβ42 plasma level and T2DM risk in the longitudinal Vienna Transdanube Aging (VITA) study cohort. Results The upstream polymorphism IDE2 was found to influence AD risk and to trigger the Aβ42 plasma level, whereas the downstream polymorphism IDE7 modified the T2DM risk; no associations were found for the intronic variant IDE9. Conclusions Based on our SNP and haplotype results, we delineate the model that IDE promoter and 3' untranslated region/downstream variation may have different effects on IDE expression, presumably a relevant endophenotype with disorder-specific effects on AD and T2DM susceptibility.